Determination of malathion's toxic effect on Lens culinaris Medik cell cycle (2020)
The present study aimed to determine the toxic effect of malathion pesticide on root growth, cell division and the chromosomal abnormalities frequency using the L. culinaris test. Initially, the lentil seeds were subjected to different doses of malathion (0.0 0.5, 1, 2.5, 5, 10, 15, 20, 25 and 30 mgL-1) and during 24, 48, and 72 h, the root length was measured. Subsequently, at 72h, the mitotic index, mitotic inhibition, and cellular abnormalities were calculated for all treatments. According to the obtained results, it was visualized that the root growth was inversely proportional to the concentration of malathion at all times of exposure. After 72h of exposure, the lowest values of the mitotic index and inhibition were presented at malathion concentrations 20, 25 and 30 mgL-1. Additionally, micronuclei cell abnormalities, metaphase sticky chromosomes, split chromosomes, nuclear lesions, irregular anaphase, anaphase bridges, binucleated cells, absence of nucleus and telophase bridge were observed. Finally, Malathion induced mitodepressive and cytotoxic effects in the meristematic cells of the L. culinaris root tip. A high frequency of abnormality was found in the micronuclei, which represented an indicator of a high degree of toxicity at the cellular level.